Pelatihan Machine Learning Menggunakan Pemrograman Python di SMK Dewantara Bekasi - Nur Hayati; F Fauziah; Novi Dian Nathasia; Harun Al Jafar; Hanni Oktaviana; Laurensius Oliver J.S; Adelia Putri H (LPPM STIKOM Tunas Bangsa, 2023)
The development of the Python programming language is currently increasing rapidly, especially in implementation into Data Science, Machine Learning, Deep Learning, Data Mining, Internet of Things and others. One of the advantages of Python programming is that it is interpretive which is usually used for prototyping, scripting in infrastructure management, to creating large-scale websites. The Python language has a very sloping learning curve, making it suitable to be learned as a first programming language with ease of reading and ease of learning its syntax. Python programming training this time is devoted to machine learning training which is intended for students of SMK Dewantara Bekasi. The material provided refers to industry standards so that later it can be implemented in the world of work. The application used is Google Colabs, which is easily accessible by logging in online through a Google account. The results of the training show that the students of SMK Dewantara Bekasi are at the Novice Programmer stage, where these students don’t understand python programming at all and the concepts of machine learning. Limited computers and internet access were also obstacles in the implementation of this training activity.